Evaluation of Liquid Nitrogen Storage for Preservation of Group A Streptococcal M Protein-Sensitized Sheep Red Blood Cells - Mathews, James H. (1970)
Streptococcal M protein-sensitized sheep red blood cells stored in liquid nitrogen showed insignificant change in titer when tested against homologous antisera over a 6-month period. This method eliminates much of the preparation time required for the passive hemagglutination procedure and increases the reproducibility of the test.